History of privatized corrections - Harding, Richard W. (Criminology & public policy, 2019)
In this historical review of prison privatization, we identify interconnected events in the UnitedStates, Australia, and the United Kingdom and their dis-tinctiveness from other nations. The political and economic catalysts for the post-1980 reemergence of privatization arealso analyzed. Privatization exists on a continuum fromancillary service delivery to full custodial operations and management. As privatization seems to have lost some ofits momentum, it is unclear whether its advent has produced the intended system-wide improvements.